My way - Anka, Paul 1941- (St. Martin's Press, 2013)
The singer/songwriter explores his life and career, from 1950s teen idol to continued success in the decades since
Keywords: Anka, Paul; Anka, Paul -- 1941-; Singers / United States / Biography; Canadian Americans / Biography; USA; Autobiografie